Biochemical characterization of a temperature responsive two-component regulatory system from the Antarctic methanogen, Methanococcoides burtonii - Najnin, Tahria (UNSW Sydney, 2016)
Temperature is a critical environmental factor that influences microbial growth. A few studies have shown that two component regulatory systems (TCSs) in bacteria may regulate temperature-dependent gene expression. TCSs typically consist of a sensor histidine kinase (SK) that responds to an extracellular signal by phosphorylating a cytoplasmic response regulator (RR) that in turn regulates gene expression. Although TCSs are present in Archaea they are poorly studied. Methanococcoides burtonii is a psychrophilic methanogen, isolated from cold (1-2 °C) methane saturated anaerobic bottom waters of Ace Lake, Antarctica. The genome sequence contains one RR, LtrR, which contains a DNA binding output domain and the gene forms an operon with a SK, LtrK. Comparative proteomic and transcriptomic analyses of M. burtonii identified higher abundance of LtrR and/or LtrK at low (4°C) compared to high (23 °C) temperature suggesting that this TCS may be involved in regulating global gene expression in response to growth temperature. The aim of this dissertation was to study the activity and stability properties of this TCS and determine whether it exhibits temperature responsive activity. To achieve this, a truncated version of LtrK lacking its N-terminal transmembrane domains was purified. The recombinant protein was able to autophosphorylate and perform phosphotransfer to LtrR as well as dephosphorylate LtrR. Analysis of the effect of temperature on LtrK found high activity at 0 °C, optimal activity at 10 °C (half-life ~ 2.8 days), reduced activity at 15 °C, and very low activity at 30 °C (half-life ~24 min). The analyses of thermal stability of LtrK showed that LtrK unfolds irreversibly with unfolding occurring at low temperatures implying that LtrK is thermolabile. The fact that the protein is intrinsically unstable and performs phosphotransfer reactions optimally at low temperatures suggests that LtrK is temperature responsive and that its cytoplasmic domain is the ‘temperature sensing’ module. The temperature-responsive properties of LtrK are likely to be important physiologically as M. burtonii is capable of growth from -2.5 to 29 °C; growth characteristics that align well with the biochemical properties of LtrK. These findings shed light on a temperature sensing TCS in a psychrophile for the first time.